Online registration for ECRL, PLKI-ECRL courses open till tomorrow - UMP, PNC (The New Straits Times Press (M) Bhd., 2018)
KUALA LUMPUR: Malaysia Rail Link Sdn Bhd's (MRL) training programme's online registration is now open until tomorrow.